Association between ER and HER2neu status with various sonographic findings in breast cancer - Abo Dega, Farah (Karbala Journal of Medicine, 2024)
Diagnostic ultrasonography is often used as a radiological modality for assessing clinically or radiologically suspected mammary lesions based on certain radiological criteria. This study was conducted to investigate an association between breast sonographic findings and biological markers (ER and HER2\NEU). The study enrolled 100 histological sample of invasive mammary carcinoma diagnosed by core needle biopsy, 52% from the right breast and 48 % from the left one , age range of patient was from 28 to 80 years with a mean age was 53 years. 64 % were estrogen receptor positive, 54% were HER2\NEU positive. There is a significant statistical correlation between ER and HER2\NEU positivity with the simultaneous presence of axillery lymph node metastasis. While there is a non statistical relashioship between ER and HER2\NEU positivity with various sonographic findings in invasive mammary carcinoma. Thus, breast ultrasound based findings are of no help to predict ER and HER2 status of invasive mammary carcinoma.